1973
DOI: 10.1001/archinte.1973.00320070097011
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Clearance of Aerosols

Abstract: The alveolar region of the lungs is endowed with several "cleansing" mechanisms whereby nongaseous substances of intrinsic and extrinsic origins are continuously removed. Collectively, the clearance mechanisms and pathways can be categorized into those effecting the removal of the readily transportable materials, eg, dissolved or monomeric substances, by passive and active absorption processes; and of the more persistent, less easily transportable materials, eg, "insoluble" dusts, by endocytosis and dissolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1975
1975
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(3 citation statements)
references
References 78 publications
(1 reference statement)
0
3
0
Order By: Relevance
“…Furthermore, they can carry organic molecules of different sort, possibly correlated to the onset of inflammatory processes in the body in relation to their accumulation. Already, in 1973, it was stated that solubility of particles may affect measurements of clearance and deposition (Morrow, 1973). Furthermore, it has also been noticed that if insoluble particles reach the alveoli, they will mainly be cleared by macrophagial phagocytosis and be transported to the ciliated airways where they are cleared out, a process that may take several years (Philipson et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they can carry organic molecules of different sort, possibly correlated to the onset of inflammatory processes in the body in relation to their accumulation. Already, in 1973, it was stated that solubility of particles may affect measurements of clearance and deposition (Morrow, 1973). Furthermore, it has also been noticed that if insoluble particles reach the alveoli, they will mainly be cleared by macrophagial phagocytosis and be transported to the ciliated airways where they are cleared out, a process that may take several years (Philipson et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is true that prolongation of pulmonary dust retention can have other bases than being induced by functional overloading or by pathological compromise of clearance mechanisms, (53)(54)(55)(56) there is scant direct evidence for the underlying mechanism in most reported studies. For example, one feature for suspecting a functional overload in contradistinction to a compartmental effect would be evidence of a threshold dust concentration in pulmonary tissue for the onset of a prolongation of retention and concomitantly a virtual cessation of dust clearance.…”
Section: The Concept Of Overloading the Lungsmentioning
confidence: 99%
“…After reaching the alveoli, most of the inhaled carbon particles are released back in the air during exhalation . The remaining particles are excreted via the lymphatic route either by flowing directly into the lymphatic system or through phagocytosis by alveolar macrophages . Experimental studies using animal models have shown that carbon particles injected into the alveoli were excreted through the lymphatic system …”
Section: Introductionmentioning
confidence: 99%